Trends Modern Games in English Language Learning For Young Learners: A Systematic Literature Review - Munawaroh, Tatu; Aulia, Rivan Fatwa; Janah, Miftahul; Sahrudin, Asep (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2025)
ABSTRACK Modern games are type of game that is loved in the midst of technological sophistication. This study aims to analyze modern games in english language for young readers from research articles. A systematic review was conducted in this study to show the findings of relevant studies on modern games that are often used in schools. Three criteria were used for the systematic review: modern game, english language, and young learner. Based on search, only six articles were included in a systematic review out of 100 articles screened by criteria; Modern Game in English Language from 2019 to 2024. The results of this study show the tendency of modern use of games into learning media, the tendency of English materials into learning content, and finally the tendency of technological involvement in producing learning media. Following up on this research, the tendency of technological and gaming touches can be integrated to design a new framework for the development of English learning technology. These findings are directed so that teachers or educators can develop English learning easily and interestingly. So that young learners are more motivated to learn together.